REMINERALIZATION OF PRIMARY MOLAR DENTINE WITH SILVER DIAMINE FLUORIDE AND SODIUM FLUORIDE : AN IN VITRO STUDY - Neslihan Yılmaz; Mert Ocak; Zeynep Ökte (Cumhuriyet University, 2020)
ABSTRACT Objectives: Silver diamine fluoride (SDF) offers a minimally invasive and inexpensive alternative to traditional restorative caries treatment. Aim of this study was to evaluate the mineral density value and remineralization effect of 38% SDF solution and 5% sodium fluoride (NaF) varnish on artificial primary tooth dentin caries lesions. Materials and Methods: 54 extracted sound primary molars were demineralized and allocated into two groups: SDF and NaF groups. After pH-cycling, mineral density values (MDV) were assessed with micro computed tomography (micro-CT) and surface morphology were studied via scanning electron microscopy (SEM). Results: After remineralization agents were apllied and specimens pH-cycled, the MDVs of the Region of Interest (ROI) in lesions increased in both NaF and SDF group. The mean MDV of SDF applied specimens was found to be higher than NaF applied specimens at statistically significant level. In the SEM images, it was observed that the dentinal tubules orifices were occluded almost completely in SDF group while the orifices in NaF group were partially occluded. Conclusions: The use of 38% SDF demonstrated a great remineralization effect on primary molar dentin than 5% NaF varnish. Further clinical studies are needed to investigate the effect of 38% SDF on primary molars which remains in the mouth longer than incisors and have a great function on chewing.